Pengaruh Kualitas Pelayanan Terhadap Keinginan Belanja Konsumen - Permana, Dewa Gde Yoga; Putra, I Putu Dharmawan Suryagita Susila; Danendra, Anak Agung Ngurah Bagus (Universitas Tabanan, 2024)
One of the main cornerstones of the Indonesian economy is MSMEs and have an impact on the growth of the Indonesian economy. One of the gatherings of MSME entrepreneurs is on the traditional market. In Indonesia today, there are still a lot of traditional markets, and the traditional market competes with e-commerce and modern markets like malls. In order for traditional markets to remain competitive, there needs to be a desire to buy from consumers. In this study, we investigated the influence of the quality of service provided on consumer spending desire with a quantitative method and with a sample size of as many as 50 respondents. For data analysis, use simple regression. In this study, a questionnaire is used to compile, and the Likert scale is used as a measure. This research shows that the quality of service can affect the desire to buy.